Navigating Digital Transformation: A Qualitative Study of Innovation Adoption in Traditional Manufacturing Operations - Nurhaliza Nurhaliza (Journal of Innovation and Operational System, 2025)
Digital transformation presents both opportunities and challenges for traditional manufacturing operations; however, limited research exists on how these firms navigate the adoption of innovation. This qualitative study examines the key drivers, barriers, and strategies influencing digital transformation in traditional manufacturing environments. Using a case study approach, the research collected data through semi-structured interviews with 20 participants across five manufacturing firms, supplemented by document analysis. Thematic analysis revealed that cost constraints (65%), legacy system incompatibility (70%), and workforce resistance (55%) were the most significant barriers, while strong leadership commitment (45%) and pilot projects emerged as critical success factors. The findings align with and extend the Technology-Organization-Environment (TOE) framework by highlighting the understudied role of organizational culture in digital adoption. The study contributes to theory by proposing a contextualized model for digital transformation in traditional manufacturing, emphasizing the need for balanced technological and human-centric approaches. Practical implications suggest that manufacturers should prioritize change management, modular upgrades for legacy systems, and leadership development to facilitate smoother transitions. Policymakers may use these insights to design targeted support programs for small and medium-sized manufacturers. Future research should explore sector-specific adoption patterns and develop standardized assessment tools for digital maturity.